Continuous dielectric energy storage hybrid film and preparation method thereof

Through the method of synchronous growth of polyester in situ polymerization and inorganic components, combined with the biaxial stretching process, the problems of high energy consumption and difficulty in large-scale production of dielectric energy storage hybrid materials in the prior art are solved, and the preparation of high-performance continuous dielectric energy storage hybrid films is achieved.

CN119684654APending Publication Date: 2025-03-25SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510044088.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the preparation of dielectric energy storage hybrid materials, multiple steps are required such as surface modification of inorganic components, organic matrix synthesis and solution blending, resulting in high energy consumption, difficulty in large-scale production, and difficulty in preparing continuous dielectric energy storage hybrid films through biaxial stretching processes.

Method used

The hybrid materials are prepared by synchronizing the in-situ polymerization of polyester and the growth of inorganic components by esterification and polycondensation reaction, and a continuous dielectric energy storage hybrid film is prepared by a biaxial stretching process, avoiding multiple processing steps in solution blending.

Benefits of technology

We have achieved large-scale preparation of hybrid materials under low-carbon strategies, and prepared high-performance continuous dielectric energy storage hybrid films, which has improved dielectric energy storage performance and reduced manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684654A_ABST
    Figure CN119684654A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric energy storage, in particular to a continuous dielectric energy storage hybrid film and a preparation method thereof.The preparation method comprises the following steps that (1) a hybrid material is prepared, specifically, metal borate, organic dihydric alcohol, organic dibasic acid and auxiliaries are added into a reaction kettle, and the hybrid material is obtained through esterification and polycondensation; and (2) preparing a hybrid thin film: processing the hybrid material into the continuous dielectric energy storage hybrid thin film by using a biaxial stretching process. The continuous dielectric energy storage hybrid thin film and the preparation method thereof have the beneficial effects that in-situ polymerization of polyester and growth of inorganic components are synchronous, organic and inorganic component precursors interact on the molecular scale, mutual diffusion of an organic matrix and the inorganic components is promoted, and the continuous dielectric energy storage hybrid thin film is prepared. A hybrid structure which is completely different from inorganic components and organic matrixes is formed in a two-phase interface region. Secondly, the hybrid material is directly prepared from the monomer on a large scale, and the continuous biaxial stretching hybrid film is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dielectric energy storage, and in particular to a continuous dielectric energy storage hybrid film and a preparation method thereof. Background Art

[0002] The mutual diffusion of organic and inorganic components in hybrid materials forms a hybrid structure that is completely different from the inorganic components and the organic polymer matrix in the interface region, causing various peculiar physical and chemical responses. In recent years, a large number of research works have confirmed that ultra-low filling of inorganic components can significantly improve the physical properties of polymers, such as mechanics and dielectric energy storage. In 2020, American scholars reported for the first time the experimental data of dimethylformamide (DMF) as a solvent solution blended poly (arylether urea) (PEEU) and ~0.2 vol% Al 2 O 3 Nanocomposites improve both the dielectric constant and breakdown strength. Subsequently, domestic and foreign scholars also used solution blending or in-situ synthesis methods to prepare a series of ultra-low-filled polymer nanocomposites and discovered similar dielectric energy storage behaviors. They believe that the hybrid structure in the interface region of ultra-low-filled polymer nanocomposites forms new dipoles, contributes additional polarization, and improves the dielectric constant of the polymer. At the same time, inorganic nanoparticles can reduce the crystal size of crystalline polymers and increase crystallinity, enhance the degree of deep traps, and improve the breakdown strength of the polymer, ultimately obtaining high energy storage density dielectric energy storage materials.

[0003] The preparation of polymer hybrid materials currently mainly adopts strategies such as solution blending or in situ synthesis. However, solution blending includes multiple steps such as polymer synthesis, inorganic component surface modification, blending and solvent removal. The preparation process is complicated and has high carbon emissions. In particular, solvent removal requires long-term high-temperature and high-vacuum treatment. Secondly, the in situ synthesis strategy also requires the inorganic component surface modification and in situ polymerization to be implemented step by step, such as Figure 1 As shown. It can be seen that the process of preparing polymer hybrid materials by solution blending and in-situ synthesis strategy is complicated, especially considering the use, removal and recycling of solvents, as well as the development trend of energy conservation and emission reduction, it is difficult to mass produce and promote application. Therefore, it is necessary to develop a low-carbon strategy to prepare dielectric energy storage hybrid films.

[0004] Through the above analysis, the problems and defects of the prior art are as follows: (1) The existing preparation technology of hybrid materials requires multiple steps such as surface modification of inorganic components, synthesis of organic matrix and solution blending, which consumes a lot of energy, especially the use, removal and recovery of organic solvents, making it difficult to scale up production and promote application; (2) Since the hybrid material preparation technology is at the laboratory research level, usually only a small amount of hybrid materials can be prepared, and it is difficult to prepare a continuous dielectric energy storage hybrid film through a biaxial stretching process. Secondly, it is difficult to completely remove the organic solvent in the film through film preparation strategies such as solution casting and casting, which directly affects the dielectric energy storage performance. In addition, multiple steps lead to high manufacturing costs and low output, which also restricts large-scale production and promotion and application.

[0005] The difficulty in solving the above problems and defects is: first, a simpler method can be used to realize the molecular or nanoscale assembly of organic and inorganic components, construct a hybrid structure in the interface area of ​​the organic matrix and the inorganic components, and prepare hybrid materials; second, a low-carbon strategy is used to prepare hybrid materials on a large scale at the same time to achieve continuous biaxial stretching of dielectric energy storage hybrid films. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a continuous dielectric energy storage hybrid film prepared by a low-carbon strategy and a preparation method thereof.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: to provide a method for preparing a continuous dielectric energy storage hybrid film, comprising the following steps: Step (1) preparing a hybrid material: adding a metal borate, an organic diol, an organic dibasic acid and an auxiliary agent into a reaction kettle, and obtaining a hybrid material through esterification and polycondensation; Step (2) Preparation of hybrid film: Processing the hybrid material into a continuous dielectric energy storage hybrid film using a biaxial stretching process.

[0008] Another technical solution of the present invention is to provide a continuous dielectric energy storage hybrid film prepared by the above-mentioned method for preparing the continuous dielectric energy storage hybrid film.

[0009] The beneficial effects of the present invention are as follows: In the continuous dielectric energy storage hybrid film and preparation method thereof of the present invention, the in-situ polymerization of polyester is synchronized with the growth of inorganic components. It should be pointed out that the organic and inorganic component precursors interact with each other at the molecular scale, promote the mutual diffusion of the organic matrix and the inorganic component, and form a hybrid structure completely different from the inorganic component and the organic matrix in the two-phase interface region. Secondly, the present invention directly prepares hybrid materials on a large scale from monomers to achieve continuous biaxially stretched hybrid films. Thirdly, the organic and inorganic component precursors of the present invention interact with each other on a molecular scale, which solves the multiple processing steps of organic solvent use, recovery and removal in solution blending, and directly prepares hybrid materials on a large scale from monomers, achieving biaxial stretching to prepare continuous hybrid films, which can quickly promote the high performance and multifunctional application of hybrid films. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1It is a comparison diagram of the technical steps for preparing organic-inorganic hybrid materials in the prior art; Figure 2 It is a flow chart of a method for preparing a continuous dielectric energy storage hybrid film provided by an embodiment of the present invention; Figure 3 This is a comparison diagram of the inorganic component precursor provided by an embodiment of the present invention before and after it is dissolved in the organic polymer monomer; Figure 4 is an X-ray diffraction pattern of an inorganic component precursor and an inorganic component in a hybrid material provided by an embodiment of the present invention; Figure 5 It is a Raman spectrum diagram of the continuous dielectric energy storage hybrid film and the pure polyester film provided by the embodiments of the present invention; Figure 6 This is a scanning electron microscope image of a continuous dielectric energy storage hybrid film provided by an embodiment of the present invention; Figure 7 This is a transmission electron microscope image of a continuous dielectric energy storage hybrid film provided by an embodiment of the present invention; Figure 8 This is a comparison diagram of the dielectric constants of the continuous dielectric energy storage hybrid film and the pure polyester film provided by the embodiment of the present invention; Fig. 9 This is a comparison chart of the breakdown strength of the continuous dielectric energy storage hybrid film and the pure polyester film provided by the embodiment of the present invention; Fig.10 It is a diagram of energy storage density of a continuous dielectric energy storage hybrid film and a pure polyester film provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0011] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0012] The key technical concept of the present invention is that the existing hybrid material preparation technology requires multiple steps such as inorganic component surface modification, organic matrix synthesis and solution blending, which has high energy consumption, especially the use, removal and recovery of organic solvents; the existing hybrid film preparation technology is difficult to prepare a continuous dielectric energy storage hybrid film through a biaxial stretching process, which limits the dielectric energy storage performance and output. In addition, the multiple steps cause high manufacturing costs and low output, which also restricts large-scale production and promotion and application. In response to the problems existing in the prior art, the present invention provides a continuous dielectric energy storage hybrid film and a preparation method thereof, in which the organic and inorganic component precursors interact at the molecular scale, solving the multiple processing steps such as the use, recovery and removal of organic solvents in solution blending; secondly, the hybrid material is directly prepared on a large scale from the monomer, and the biaxial stretching is realized to prepare a continuous hybrid film, which can quickly promote the high performance and multifunctional application of hybrid films.

[0013] like Figure 2 As shown, the present invention provides a method for preparing a continuous dielectric energy storage hybrid film, comprising the following steps: Step (1) preparing a hybrid material: adding a metal borate, an organic diol, an organic dibasic acid and an auxiliary agent into a reaction kettle, and obtaining a hybrid material through esterification and polycondensation; Step (2) Preparation of hybrid film: Processing the hybrid material into a continuous dielectric energy storage hybrid film using a biaxial stretching process.

[0014] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the metal borate in step (1) is a mixture of any one or more of aluminum borate, copper borate, iron borate, barium borate, calcium borate, magnesium borate, bismuth borate, tin borate, zinc borate, thulium borate, tantalum borate, samarium borate, strontium borate, erbium borate, europium borate and cerium borate.

[0015] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the organic diol in step (1) is a mixture of any one or more of butenediol, butynediol, butanediol, ethylene glycol and hexanediol.

[0016] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the organic dibasic acid in the step (1) is a mixture of any one or more of cyclobutanedicarboxylic acid, furandicarboxylic acid, thiophenedicarboxylic acid, benzimidazoledicarboxylic acid, succinic acid, terephthalic acid, thiazoledicarboxylic acid, naphthalenedicarboxylic acid, biphenyldicarboxylic acid, fluorophthalic acid, pyridinedicarboxylic acid, maleic acid, maleic anhydride, succinic anhydride, cyclohexanedicarboxylic acid and ferrocenedicarboxylic acid.

[0017] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the auxiliary agent in step (1) is a mixture of any one or more of antimony oxide, tetrabutyl titanate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, titanate coupling agent, aluminate coupling agent, p-phenylenediamine, hexamethylenediamine, ethylenediamine and cyclohexanediamine.

[0018] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the weight ratio of each raw material in the step (1) is: 100 parts of organic diol, 0.1-10 parts of metal borate, 80-300 parts of organic dibasic acid, and 0.1-10 parts of auxiliary agent.

[0019] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the conditions for the esterification and polycondensation in step (1) are: the esterification temperature is 220-250°C, the esterification time is 3-5h, the polycondensation temperature is 250-300°C, and the polycondensation time is 1-4h.

[0020] Preferably, in the above-mentioned method for preparing the continuous dielectric energy storage hybrid film, the biaxial stretching process in step (2) is a synchronous biaxial stretching process or an asynchronous biaxial stretching process; The conditions of the synchronous biaxial stretching process are: the stretching temperature is 50-160°C, the longitudinal and transverse stretching ratios are both 3-4 times, and the heat setting temperature is 200-250°C; In the asynchronous biaxial stretching process, the longitudinal stretching temperature is 50-95°C, the longitudinal stretching ratio is 3-4 times, the transverse stretching temperature is 80-160°C, the transverse stretching ratio is 2-4 times, and the heat setting temperature is 200-250°C.

[0021] The present invention provides a continuous dielectric energy storage hybrid film prepared by the above-mentioned method for preparing the continuous dielectric energy storage hybrid film.

[0022] The continuous dielectric energy storage hybrid film and preparation method thereof provided by the present invention enable the organic and inorganic component precursors to interact at the molecular scale, thereby solving multiple processing steps such as the use, recovery and removal of organic solvents in solution blending; secondly, hybrid materials are directly prepared on a large scale from monomers, and biaxial stretching is achieved to prepare continuous hybrid films, which can rapidly promote the high performance and multifunctional application of hybrid films.

[0023] Example 1

[0024] A method for preparing a continuous dielectric energy storage hybrid film comprises the following steps: (1) Preparation of hybrid material: 100 parts of ethylene glycol, 2 parts of magnesium borate, 80 parts of terephthalic acid, 0.05 parts of dodecylbenzene sulfonic acid and 0.05 parts of antimony oxide were added into a reactor, esterification reaction was carried out at 220° C. for 3 hours, and then polycondensation reaction was carried out at 260° C. for 6 hours to prepare a hybrid material; (2) Preparation of hybrid film: A continuous hybrid film was prepared by asynchronous stretching. The film was longitudinally stretched at a stretching ratio of 4 times at 80°C, and then transversely stretched at a stretching ratio of 4 times at 130°C. The heat setting temperature was 220°C, and finally a continuous dielectric energy storage hybrid film was prepared.

[0025] Example 2

[0026] A method for preparing a continuous dielectric energy storage hybrid film comprises the following steps: (1) Preparation of hybrid material: 100 parts of ethylene glycol, 10 parts of bismuth borate, 300 parts of naphthalene dicarboxylic acid, 0.1 parts of tetra-n-butyl titanate and 9.9 parts of p-phenylenediamine were added into a reaction kettle, and esterification reaction was performed at 230° C. for 4 hours, and then polycondensation reaction was performed at 250° C. for 2 hours to prepare a hybrid material; (2) Preparation of hybrid film: A continuous hybrid film was prepared by asynchronous stretching. The film was longitudinally stretched at a stretching ratio of 3 times at 50°C, and then transversely stretched at a stretching ratio of 3 times at 80°C. The heat setting temperature was 200°C, and finally a continuous dielectric energy storage hybrid film was prepared.

[0027] Example 3

[0028] A method for preparing a continuous dielectric energy storage hybrid film comprises the following steps: (1) Preparation of hybrid material: 100 parts of ethylene glycol, 10 parts of bismuth borate, 300 parts of naphthalene dicarboxylic acid, 0.1 parts of tetra-n-butyl titanate and 9.9 parts of p-phenylenediamine were added into a reaction kettle, and esterification reaction was carried out at 250° C. for 5 hours, and then polycondensation reaction was carried out at 300° C. for 6 hours to prepare a hybrid material; (2) Preparation of hybrid film: A continuous hybrid film was prepared by asynchronous stretching. The film was longitudinally stretched at a stretching ratio of 3.5 times at 95°C, and then transversely stretched at a stretching ratio of 3.5 times at 160°C. The heat setting temperature was 250°C, and finally a continuous dielectric energy storage hybrid film was prepared.

[0029] Example 4

[0030] A method for preparing a continuous dielectric energy storage hybrid film comprises the following steps: (1) Preparation of hybrid material: 100 parts of ethylene glycol, 2 parts of iron borate, 200 parts of furandicarboxylic acid, 0.1 parts of antimony oxide and 9.9 parts of hexamethylenediamine were added into a reaction kettle, esterified at 220° C. for 3 h, and then polycondensed at 250° C. for 6 h to prepare the hybrid material; (2) Preparation of hybrid film: A continuous hybrid film was prepared by synchronous stretching. The film was stretched longitudinally and transversely at a stretching ratio of 3.5 times at 100°C and the heat setting temperature was 200°C. Finally, a continuous dielectric energy storage hybrid film was prepared.

[0031] Example 5

[0032] A method for preparing a continuous dielectric energy storage hybrid film comprises the following steps: (1) Preparation of hybrid material: 100 parts of ethylene glycol, 0.1 parts of copper borate, 80 parts of maleic acid, and 0.1 parts of antimony oxide were added into a reactor, esterified at 230° C. for 4 hours, and then polycondensed at 260° C. for 4 hours to prepare a hybrid material; (2) Preparation of hybrid film: A continuous hybrid film was prepared by synchronous stretching. The longitudinal and transverse stretching was performed at 50°C with a stretching ratio of 3 times and a heat setting temperature of 210°C. Finally, a continuous dielectric energy storage hybrid film was prepared.

[0033] Example 6

[0034] A method for preparing a continuous dielectric energy storage hybrid film comprises the following steps: (1) Preparation of hybrid material: 100 parts of ethylene glycol, 10 parts of zinc borate, 300 parts of benzimidazole dicarboxylic acid, and 0.1 parts of tetra-n-butyl titanate were added into a reactor, and esterification reaction was performed at 250° C. for 5 h, and then polycondensation reaction was performed at 300° C. for 6 h to prepare a hybrid material; (2) Preparation of hybrid film: The obtained hybrid material is subjected to simultaneous stretching to prepare a continuous hybrid film. The film is stretched longitudinally and transversely at a stretching ratio of 4 times at 160°C and the heat setting temperature is 250°C. Finally, a continuous dielectric energy storage hybrid film is prepared.

[0035] Effect verification The comparison diagram of the inorganic component precursor in the above embodiment of the present invention before and after dissolving in the organic polymer monomer is as follows: Figure 3 shown.

[0036] In the above embodiments of the present invention, the inorganic component precursor metal borate ester simultaneously regenerates to form new inorganic components during the polyester in-situ polymerization process, and the molecular structure undergoes significant changes, such as Figure 4 shown.

[0037] The continuous dielectric energy storage hybrid film (polyester hybrid film) obtained in the above embodiment of the present invention is significantly different from the pure polyester film (obtained in the prior art) in structure and morphology, such as Figures 5 to 7 shown.

[0038] The continuous dielectric energy storage hybrid film (polyester hybrid film) obtained in the above embodiment of the present invention has significantly improved dielectric energy storage performance compared with pure polyester film. Figures 8 to 10 shown.

[0039] In summary, in the continuous dielectric energy storage hybrid film and preparation method thereof of the present invention, the organic and inorganic component precursors interact with each other at the molecular scale, which solves the multiple processing steps such as the use, recovery and removal of organic solvents in solution blending, and directly prepares hybrid materials on a large scale from monomers, realizing biaxial stretching to prepare continuous hybrid films, which can rapidly promote the high performance and multifunctional application of hybrid films.

[0040] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a continuous dielectric energy storage hybrid film, characterized in that: The following steps are involved: Step (1) preparing a hybrid material: adding a metal borate, an organic diol, an organic dibasic acid and an auxiliary agent into a reaction kettle, and obtaining a hybrid material through esterification and polycondensation; Step (2) Preparation of hybrid film: Processing the hybrid material into a continuous dielectric energy storage hybrid film using a biaxial stretching process.

2. The method for preparing the continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The metal borate in step (1) is a mixture of any one or more of aluminum borate, copper borate, iron borate, barium borate, calcium borate, magnesium borate, bismuth borate, tin borate, zinc borate, thulium borate, tantalum borate, samarium borate, strontium borate, erbium borate, europium borate and cerium borate.

3. The method for preparing the continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The organic diol in step (1) is a mixture of any one or more of butenediol, butynediol, butanediol, ethylene glycol and hexanediol.

4. The method for preparing the continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The organic dibasic acid in step (1) is a mixture of any one or more of cyclobutanedicarboxylic acid, furandicarboxylic acid, thiophenedicarboxylic acid, benzimidazoledicarboxylic acid, succinic acid, terephthalic acid, thiazoledicarboxylic acid, naphthalenedicarboxylic acid, biphenyldicarboxylic acid, fluorophthalic acid, pyridinedicarboxylic acid, maleic acid, maleic anhydride, succinic anhydride, cyclohexanedicarboxylic acid and ferrocenedicarboxylic acid.

5. The method for preparing the continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The auxiliary agent in step (1) is a mixture of any one or more of antimony oxide, tetra-n-butyl titanate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, dodecyldimethylbenzyl ammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, titanate coupling agent, aluminate coupling agent, p-phenylenediamine, hexamethylenediamine, ethylenediamine and cyclohexanediamine.

6. The method for preparing the continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The weight ratio of the raw materials in step (1) is: 100 parts of organic diol, 0.1-10 parts of metal borate, 80-300 parts of organic dibasic acid, and 0.1-10 parts of auxiliary agent.

7. The method for preparing a continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The conditions for the esterification polycondensation in step (1) are as follows: the esterification temperature is 220-250° C., the esterification time is 3-5 hours, the polycondensation temperature is 250-300° C., and the polycondensation time is 1-4 hours.

8. The method for preparing the continuous dielectric energy storage hybrid film according to claim 1, characterized in that: The biaxial stretching process in step (2) is a synchronous biaxial stretching process or an asynchronous biaxial stretching process; The conditions of the synchronous biaxial stretching process are: the stretching temperature is 50-160°C, the longitudinal and transverse stretching ratios are both 3-4 times, and the heat setting temperature is 200-250°C; In the asynchronous biaxial stretching process, the longitudinal stretching temperature is 50-95°C, the longitudinal stretching ratio is 3-4 times, the transverse stretching temperature is 80-160°C, the transverse stretching ratio is 2-4 times, and the heat setting temperature is 200-250°C.

9. A continuous dielectric energy storage hybrid film prepared according to the method for preparing a continuous dielectric energy storage hybrid film according to any one of claims 1 to 8.